Factors influencing turnover intention for registered nurse at KPJ Johor Specialist Hospital / Mohd. Fais Ismail, Nuramalina Selamat and Nurul Nadiah Mohd Nor - Ismail, Mohd. Fais; Selamat, Nuramalina; Mohd Nor, Nurul Nadiah (2023)
The registered nurse is a valuable asset at KPJ Johor Specialist Hospital, contributing significantly to the organization's performance in a competitive market. However, turnover intentions among registered nurses have become a significant hurdle to the organization's productivity and services as they have increased yearly. This study was intended to determine the relationship between Economic Factors, Work Conditions, Management-Related Factors, and Individual Factors related to Registered Nurses' Intention to Resign from KPJ Johor Specialist Hospital. This study employed a quantitative methodology, non-probability sampling was used in which a questionnaire would be collected from the respondents. One hundred ninety KPJ Johor Specialist Hospital registered nurses participated in the study. The data were collected and analysed using a Social Science Statistical Package (SPSS). Using multiple regression analysis, the significance lies in determining which factors impact turnover intention of registered nurses at KPJ Johor Specialist Hospital. The findings reveal that work conditions, management-related factors, and individual factors significantly influence turnover intention. Negative perceptions of work conditions, including workload and administrative burden, as well as dissatisfaction with the physical work environment, contribute to higher turnover intention. Management related factors such as recognition, appreciation, career advancement opportunities, effective communication, and training provision also play crucial role in nurses' decision to stay or leave the organisation. Individual factors significantly influence turnover intention, including intrinsic motivation, personal life events, and work-life balance. To mitigate turnover intention, recommendations have been proposed including improving work conditions, enhancing management practices, supporting individual well-being, promoting a culture of continuous improvement and collaboration, and providing professional development opportunities. By implementing these recommendations, KPJ Johor Specialist Hospital can create a supportive and engaging work environment that addresses the key factors that influence turnover intention, leading to higher nurse retention and overall organisational success. Future research could focus on longitudinal studies to track turnover intention among registered nurses over an extended period and investigate the effectiveness of implemented retention programmes.